2021
DOI: 10.1109/tc.2020.3038063
|View full text |Cite
|
Sign up to set email alerts
|

Credit Risk Analysis Using Quantum Computers

Abstract: We present and analyze a quantum algorithm to estimate credit risk more efficiently than Monte Carlo simulations can do on classical computers. More precisely, we estimate the economic capital requirement, i.e. the difference between the Value at Risk and the expected value of a given loss distribution. The economic capital requirement is an important risk metric because it summarizes the amount of capital required to remain solvent at a given confidence level. We implement this problem for a realistic loss di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
112
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 94 publications
(118 citation statements)
references
References 36 publications
0
112
0
Order By: Relevance
“…This allows us to define trial wavefunctions |ψ H(y) (θ) that now depend on y. As in (5) we can translate the MBO to a continuous optimization problem, where the measurements x j (θ, y) depend on θ as well as y. In summary, A(y), b(y), and c(y) define the Hamiltonian H(y), which in turn defines the θand y-dependent trial wavefunction |ψ H(y) (θ) .…”
Section: Quantum Optimization Algorithms For Mbomentioning
confidence: 99%
See 2 more Smart Citations
“…This allows us to define trial wavefunctions |ψ H(y) (θ) that now depend on y. As in (5) we can translate the MBO to a continuous optimization problem, where the measurements x j (θ, y) depend on θ as well as y. In summary, A(y), b(y), and c(y) define the Hamiltonian H(y), which in turn defines the θand y-dependent trial wavefunction |ψ H(y) (θ) .…”
Section: Quantum Optimization Algorithms For Mbomentioning
confidence: 99%
“…Next, we introduce a heuristic that is designed to handle slack variables resulting from modelling inequality constraints explicitly. This can help the classical optimizer used to solve (5) to move out of local minima. Suppose, for simplicity, that we have a problem with only binary variables and a single slack variable, coming from an inequality constraint, formally given by…”
Section: Quantum Optimization Algorithms For Mbomentioning
confidence: 99%
See 1 more Smart Citation
“…Quantum Amplitude Estimation (QAE) 1 is a fundamental quantum algorithm with the potential to achieve a quadratic speedup for many applications that are classically solved through Monte Carlo (MC) simulation. It has been shown that we can leverage QAE in the financial service sector, e.g., for risk analysis 2,3 or option pricing [4][5][6] , and also for generic tasks such as numerical integration 7 . While the estimation error bound of classical MC simulation scales as Oð1= ffiffiffiffi M p Þ, where M denotes the number of (classical) samples, QAE achieves a scaling of Oð1=MÞ for M (quantum) samples, indicating the aforementioned quadratic speedup.…”
Section: Introductionmentioning
confidence: 99%
“…Quantum computers are theoretically proven to solve certain problems faster than a classical device [1][2][3] and are well-equipped to handle tasks such as factoring [2], linear systems of equations [4,5], Monte-Carlo simulations [6][7][8][9], as well as combinatorial optimization problems [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%